2017
DOI: 10.48550/arxiv.1707.05240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coloring Down: $3/2$-approximation for special cases of the weighted tree augmentation problem

Abstract: In this paper, we investigate the weighted tree augmentation problem (TAP), where the goal is to augment a tree with a minimum cost set of edges such that the graph becomes two edge connected. First we show that in weighted TAP, we can restrict our attention to trees which are binary and where all the non-tree edges go between two leaves of the tree. We then give two different top-down coloring algorithms. Both of our algorithms differ from known techniques for obtaining a 3 2 -approximation in unweighted TAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The best-known approximation factor for this problem is 2 [FJ81], but when the solution is half-integral, there is a 4 3 -approximation [CJR99]. This latter result has been generalized by Iglesias and Ravi [IR17].…”
Section: Outline and Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-known approximation factor for this problem is 2 [FJ81], but when the solution is half-integral, there is a 4 3 -approximation [CJR99]. This latter result has been generalized by Iglesias and Ravi [IR17].…”
Section: Outline and Organizationmentioning
confidence: 99%
“…Theorem 6 (Iglesias and Ravi [IR17]). If y ∈ Cover(G, F ) and y e ≥ α or y e = 0 for all e ∈ E, then there is an algorithm, whose running time is polynomial in the size of G, that writes the vector 2 1+α • y as a convex combination of 1-covers C 1 , .…”
Section: Tree Augmentationmentioning
confidence: 99%
“…A recently fruitful such special case has been the assumption that solutions to the relevant linear program (LP) are half-integral-that is, each coordinate of an optimal solution is assumed to lie in {0, 1 2 , 1}. Notably, Cheriyan et al [4] showed that WTAP admits a 4 3-approximation if the relevant LP is half-integral and Iglesias and Ravi [15] generalized this by showing that a 2 (1 + f )-approximation is possible for WTAP if non-zero LP values are assumed to be at least f > 0. Similarly, a recent breakthrough of Karlin et al [17] showed that a ≈ 1.49993 approximation is possible for TSP if the LP solution is assumed to be half-integral.…”
Section: Introductionmentioning
confidence: 99%